استخراج أصول الأدلة العقلية العقدية من العقيدة البرهانية لأبي عمرو عثمان السلالجي (ت: 574ه- Extracting the source of theological logic evidence from “al-ʿAqīdah al-Burhāniyyah” by Abū ʿAmr ʿUthmān al-Salālajī‚ (Died 574 H) - al-Akiti, Muhammad Ayman (IIUM Press, International Islamic University Malaysia, 2019)
The book “al-ʿAqīdah al-Burhāniyyah” is a book of theology in Ashʿari’s school and it played a very important role to officialise the Ash'ari faith in the western part of Islamic world. It was officially used in the oldest university in the world; the University of Qarawiyyen in Fez. This proves how important this book is, as it becomes the pillar for the Sanussi’s creed which is a major prevailing creed for Ash’ari’s school in the ninth century AH to the present day. This book was written by one of the greatest Ashairah scholars of the western part of Islamic world, which is Imam Abū ʿAmr ʿUthmān al-Salālijī‚, who lived in the period of the Almoravids and Almohads and died in 574 AH. He was a student at University of Qarawiyyīn in Fez and later become a professor there. He is also one of those who greatly responsible for the wide spreading of the Ash'ari’s school in the western part of the Islamic world; and making it the official and most followed schools for the people there, specifically in the Kingdom of Morocco who remain firm in Ashāʿirah school till today. Although this book is not well known in this era, it is not because of its absence of added value that could benefits our researchers today, instead, it contains many important issues and theological inferences, such as "the invalidity of evidence/causation does not authorize the invalidity of the meaning/cause", and "inference: validity of one thing can relies on the validity of his counterparts/equal, while on the same basis, his invalidity/impossibility can also relies on the invalidity/impossibility of his counterparts/equal" and others. On this basis, this book was called "Prooved Creed"; full of explanation based on logical argument and reasoning. As we already know that Islamic theology and belief was based on arguments and evidence, it is important to also realise the necessity of knowing the methods and inference. The method and the process to reach the result/goal is considered as important as the result itself; if the process/methodology is corrupted, the results will also be corrupted, and likewise if the process/methods is valid then the result follows. Without the correct methodology, we are like such a doctor who seeks to treat his patients by treating the symptoms rather than the disease that led to it. Application of the treatment is useless as long as the origin of the disease remains in the patient's body. Systematic and methodological study is important in revealing the “truth” of the evidence/symptom of it. In order to achieve this purpose, I wanted my article and my work in this symposium to be on the analysis of this book, specifically on the part of deriving the theological evidence on which it was built, thus the title for this paper is justified: Extracting the source of theological logic evidence from “al-ʿAqīdah al-Burhāniyyah” by Abū ʿAmr ʿUthmān al-Salālijī (died 574 H).